Strategia wykorzystania przez Polskę Funduszu Spójności na lata 2004-2006 - Sporek, Tadeusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The strategy for the availing of the Cohesion Fund has been elaborated under the assumption that the main objective to be realized in the years 2004-2006, and in the following years, shall be to enhance the competitiveness of the Polish economy and to strive towards the social and economic cohesion within the enlarged Community. The Cohesion Fund supports measures of the National Development Plan through "the creation of suitable conditions for the increase in the level of investments, the promotion of sustainable development and territorial cohesion". The main priorities in the years 2004-2006 shall be: the improvement of the quality of surface waters, flood safety, rational waste management and the improvement of air quality. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 329-338